Evaluation of four-terminal-pair capacitance standards using electrical equivalent circuit model. (September 2015) - Satish; Babita; Khurana, Bharat; Kumar, Sachin; Saxena, A.K.
Graphical abstract: Highlights: We have evaluated 4TP capacitance standards of Agilent 16380A type from 10 kHz to 30 MHz. Evaluated standards will be used to establish national standards for capacitance. Integrated measurement automation program controls the each step of evaluation procedure. Uncertainty measurement for 4TP standard is computed as per GUM document. Uncertainty due to C 00, C HG and C LG has significant impact on final uncertainty in measurement. Abstract: The reported work has been performed in order to establish the measurement traceability of high frequency capacitance standards at CSIR-NPL. In this context, four-terminal-pair air capacitance standards of Agilent 16380A type with nominal values of 1 pF, 10 pF, 100 pF and 1000 pF have been evaluated at a set of frequencies ranging from 10 kHz to 30 MHz. The evaluation procedure involves the determination of capacitive and inductive residual components of an electrical equivalent circuit model of these standards. The versatile measurement automation program has been developed to control the evaluation procedure and the functionality of the same has been discussed in the paper.